A family with Milroy disease caused by the FLT4/VEGFR3 gene variant c.2774 T > A - Yu Sui; Yongping Lu; Meina Lin; Xiang Ni; Xinren Chen; Huan Li; Miao Jiang (BMC, 2021)
Abstract Background Milroy disease (MD) is a rare, autosomal-dominant disorder. Variants in the Fms-related tyrosine kinase 4 (FLT4/VEGFR3) gene cause the symptoms of this disease. In this report, we investigated the variant in a large Chinese family with MD. Methods We conducted Sanger sequencing of exons 17-26 of FLT4/VEGFR3 (NM_182925.4). We assessed its pathogenicity based on the ACMG criteria and predicted it with an in silico program. Results A heterozygous substitution (NM_182925.4 (FLT4/VEGFR3):c.2774 T>A, p. (Val925Glu)) was detected in all patients with MD but not in any healthy controls. The variant was evaluated as pathogenic according to the ACMG criteria and was predicted to be pathogenic using an in silico program. Conclusions In this report, we described a large family with MD caused by a missense variant in FLT4/VEGFR3 (NM_182925.4 (FLT4/VEGFR3_v001):c.2774 T>A, p. (Val925Glu)). There are phenotypic heterogeneities among family members, and further research should be conducted to explore the possible reasons.